2001
DOI: 10.1176/appi.ajp.158.7.1075
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical Correlates of Craving in Recently Abstinent Alcoholic Patients

Abstract: This investigation points to state-dependent neurobiological correlates of cue-induced craving in alcoholic patients and suggests that these correlates can be influenced by therapeutic interventions. The presence of emotional aspects of craving is suggested by amygdala activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
215
2
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(240 citation statements)
references
References 35 publications
13
215
2
10
Order By: Relevance
“…From these findings, we conclude that axonal DAT-IR-enriched vermis lobules are activated by cocainerelated cues. The vermis also is activated during stimulant expectancy (Volkow et al, 2003) and in alcoholics during alcohol odor cue-induced craving (Schneider et al, 2001), implying that it may generally activate in response to drugassociated stimuli in drug abusing cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these findings, we conclude that axonal DAT-IR-enriched vermis lobules are activated by cocainerelated cues. The vermis also is activated during stimulant expectancy (Volkow et al, 2003) and in alcoholics during alcohol odor cue-induced craving (Schneider et al, 2001), implying that it may generally activate in response to drugassociated stimuli in drug abusing cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Acute administration of or cues for other stimulants or psychoactive drugs also has been associated with increased cerebellar activity (Volkow et al, 1996(Volkow et al, , 1988London et al, 1990;Ghatan et al, 1998;Sell et al, 1999;Domino et al, 2000). Two studies reported cerebellar midline (vermis) activation by alcohol odor cues and by stimulant expectancy (Schneider et al, 2001;Volkow et al, 2003). Such findings are intriguing in light of reports localizing DAT immunoreactivity (DAT-IR) and mRNA in primate cerebellar vermis (Melchitzky and Lewis, 2000;Hurley et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In einer Studie zeigten detoxifizierte Alkoholpatienten Cravingphänomene bei der Präsentation alkoholassoziierter Reize, was im fM-RI mit einer Aktivierung der Amygdala einherging. Die Kontrollgruppe dagegen zeigte keinerlei derartige Veränderungen [45]. Nach 3-wöchiger Verhaltenstherapie und Gabe von Antidepressiva zeigten die Testpersonen ein deutlich gesenktes Craving.…”
Section: Oxytocin Im Einsatz Gegen Suchtmechanismenunclassified
“…Nach 3-wöchiger Verhaltenstherapie und Gabe von Antidepressiva zeigten die Testpersonen ein deutlich gesenktes Craving. Die Amygdalaaktivität im fMRI war nun nicht mehr abweichend von der Aktivität der Kontrollpersonen [45]. Diese Befunde unterstreichen die These, dass die Beeinflussung von Stress und die Senkung der CRF-Aktivität in der Amygdala durch Oxytocin zielführend sein könnten.…”
Section: Oxytocin Im Einsatz Gegen Suchtmechanismenunclassified
“…Furthermore, this work demonstrated that taste and visual cues could induce brain activation in alcoholics within the MRI environment. Two subsequent studies have utilized fMRI with visual (Braus et al, 2001) or olfactory (Schneider et al, 2001) cues. These studies found activation of the putamen as well as the subcortical-limbic region and cerebellum, respectively.…”
Section: Introductionmentioning
confidence: 99%